Legal Protection of Creditors' Preferences Rights Regarding Fiduciary Security Receivables - Muhammad Awal Alishakur; Ariawan Gunadi (Dinasti Research, 2024)
This article is entitled legal protection of creditors' preference rights for fiduciary guarantee receivables. This article uses a normative legal research type with a research approach . statute approach , namely a legislative approach carried out by identifying legal issues and discuss applicable laws and regulations, in relation to the material discussed . The state through laws and regulations provides legal protection for recipients of guarantees for goods legally in the transfer of rights to goods, one of which is fiduciary guarantees. This guarantee positions the recipient of the guarantee as having special rights, namely being given the first opportunity in terms of making payments if the borrower experiences default or bankruptcy . The recipient of fiduciary guarantees legally according to the Fiduciary Law can sell goods that have been placed as fiduciary guarantees, if the creditor or borrower cannot fulfill their obligations in the loan agreement. This execution is guaranteed in Article 15 paragraph (2) of the Fiduciary Law, through an execution mechanism with a court ruling